Investigating Stimulation Protocols for Language Mapping by Repetitive Navigated Transcranial Magnetic Stimulation - Sollmann, Nico; Fuss-Ruppenthal, Sophia; Zimmer, Claus; Meyer, Bernhard; Krieg, Sandro M. (Frontiers in Behavioral Neuroscience, 2018)
Navigated transcranial magnetic stimulation (nTMS) is increasingly applied to map human language functions. However, studies on protocol comparisons are mostly lacking. In this study, twenty healthy volunteers (25.7 ± 3.8 years, 12 females) underwent left-hemispheric language mapping by nTMS, combined with an object-naming task, over a cortical spot with reproducible naming errors within the triangular or opercular part of the inferior frontal gyrus (trIFG, opIFG: anterior stimulation) and the angular gyrus or posterior part of the superior temporal gyrus (anG, pSTG: posterior stimulation), respectively. Various stimulation intensities (80%, 100%, and 120% of the resting motor threshold [rMT]), frequencies (2 Hz, 5 Hz, 10 Hz, and 20 Hz), and coil orientations (in steps of 45°) were evaluated, and the adjustments leading to the highest error rates (ERs), combined with low occurrences of errors due to muscle stimulation, were considered optimal. Regarding anterior stimulation, 100% rMT, 5 Hz, and a coil orientation of 90° or 270° in relation to the respective stimulated gyrus resulted in optimal results. For posterior stimulation, 100% rMT, 10 Hz, and coil orientations of 90° or 270° were considered optimal. Errors due to facial muscle stimulation only played a considerable role during analyses of high-intensity (120% rMT) or high-frequency stimulation (20 Hz). In conclusion, this is one of the first studies to systematically investigate different stimulation protocols for nTMS language mapping, including detailed analyses of the distribution of ERs in relation to various coil orientations considered during neuronavigated stimulation. Mapping with 100% rMT, combined with 5 Hz (anterior stimulation) or 10 Hz (posterior stimulation) and a coil orientation perpendicular to the respective stimulated gyrus can be recommended as optimal adjustments.